Green Growth and Climate Change in Uzbekistan Policy Dialogue Series : A Compendium of Proceedings - World Bank (Washington, DC : World Bank, 2022)
Over the last few decades, Uzbekistan’s remarkable economic growth has been largely fueled by resource extraction and the mining and manufacturing sectors of the economy. Yet, this progress has come at a high price. The country’s economy is now the fifth most intensive in terms of greenhouse gas (GHG) emissions in the world and the most intensive in Europe and Central Asia due to a fossil-fuel heavy energy mix, an energy-intensive industrial sector, and low energy efficiency across the sectors. Like the rest of Central Asia, Uzbekistan is also highly vulnerable to climate change. Recently, many regions in Uzbekistan, including Tashkent, experienced an unprecedented sand and dust storm, the worst in 150 years of recorded history. Green transition is also important for the people of Uzbekistan, who are the most vulnerable to climate change. The Coronavirus (COVID-19) pandemic has added yet another shock to the compounding impacts of many challenges that vulnerable populations already face, with the potential to create devastating health, social, economic, and environmental crises that can leave a deep and long-lasting mark. Today, Uzbekistan recognizes a unique opportunity to overcome limits to growth under its current development pattern and to strengthen its economic competitiveness in a global marketplace that has become more climate and environmentally aware. Pursuing a green transition with widespread benefits requires a whole-of-society approach that considers a broad range of stakeholders. To that end, the Ministry of Economic Development and Poverty Reduction of the Republic of Uzbekistan (MEDPR), The World Bank, and the Regional Environmental Center for Central Asia (CAREC) jointly held a series of public policy dialogues on green growth and climate change. The World Bank Group remains committed to continuing to be a trusted partner of the government Uzbekistan. Summaries of the eleven policy dialogue roundtables presented in this compendium should inspire many other countries in Europe and Central Asia to follow Uzbekistan’s lead on this agenda.